2012
DOI: 10.1002/cnm.2488
|View full text |Cite
|
Sign up to set email alerts
|

Numerical treatment of boundary conditions to replace lateral branches in hemodynamics

Abstract: In this paper, we discuss a technique for weakly enforcing flow rate conditions in computational hemodynamics. In particular, we study the effectiveness of cutting lateral branches from the computational domain and replacing them with non-perturbing boundary conditions to simplify the geometrical reconstruction and the numerical simulation. All these features are investigated both in the case of rigid and compliant walls. Several numerical results are presented to discuss the reliability of the proposed method. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 44 publications
(110 reference statements)
0
24
0
Order By: Relevance
“…In addition, it deals with non standard bilinear forms that require ad hoc implementation. Two dimensional numerical results shown in [209] highlight the accuracy of the method, whereas three-dimensional results reported in [158] demonstrate that this is an effective approach for real applications. A similar approach has been extended to fulfill the mean pressure condition (20) and the FSI case in [198].…”
Section: Further Developments and Commentsmentioning
confidence: 89%
“…In addition, it deals with non standard bilinear forms that require ad hoc implementation. Two dimensional numerical results shown in [209] highlight the accuracy of the method, whereas three-dimensional results reported in [158] demonstrate that this is an effective approach for real applications. A similar approach has been extended to fulfill the mean pressure condition (20) and the FSI case in [198].…”
Section: Further Developments and Commentsmentioning
confidence: 89%
“…In the last years, different variants of Equation 11 have been proposed in the literature in the context of physiological flows, all of them independent from the original work. 14 In particular, the choice u 0 = 0 has been widely used in both hemodynamics [16][17][18][19] and respiratory regimes. 20,21 While ⩾ 1 assures energy stability, the numerical results of Esmaily et al 18 showed that decreasing the value of the parameter up to = 0.4 still yields stable solutions in the case of blood flow, thus suggesting that the lack of stability (and hence the magnitude of the required stabilization) depends on the considered flow regime.…”
Section: Velocity-penalization Methodsmentioning
confidence: 99%
“…23 A uniqueness result in the case of small data for ⩾ 1 can be found in Braack and Mucha. 24 It is worth mentioning that, for sufficiently small data, the analysis of Baffico et al 25 A further variant was proposed by Porpora et al, 19 where u 0 was taken as a plug profile for a given flow rate at the inlet of the ascending aorta.…”
Section: Velocity-penalization Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then it leads to difficulties that we will investigate in this paper. Although this basic form is often used (see, e.g., [40,58,74,75,22,62,31,55,1]), some numerical studies (see, e.g., [40,31]) have pointed out that the stability is not guaranteed when dealing with realistic physiological or physical parameters.…”
Section: Introductionmentioning
confidence: 99%